Aspectos de radioproteção em radiologia veterinária na cidade de Curitiba - Paraná - Rosa, Paola da Costa (2018)
Radiology is a widely used modality in veterinary medicine, weak to good availability and cost. However, the lack of regulations for practice in Brazil can cause a compromise in the radiological safety and quality aspects of the facilities that perform the practice. For this reason, it was sought to identify the radioprotection aspects of veterinary facilities that have X-ray equipment in the city of Curitiba, based on the verification of the conditions of X-ray equipment, the documentation presented, the existence of individual monitoring and the existence of lead clothing, and of the architectural features of the rooms. The data was collected through quantitative field research of a descriptive nature during the period from March 2016 to December 2017. Volunteers from clinics, hospitals and educational establishments that had Xray equipment in the city of Curitiba. The sample consisted of 31 establishments and 32 equipments. With the result of the research, it was possible to emphasize that 90% of the installations had radioprotection project and scattering measurement. Quality control existed in 45% of installations and radiation protection plan in 6% of facilities. Only 3% of the equipment meets the quality characteristics of the X-ray equipment described in Resolution 1016. However, 64% of the personal dose readings were background level. No room was found with minimal spacing of the barriers from the focal point greater than 1.5m. Veterinary radiology procedures can be optimized, especially with the use of adequate exposure techniques, physical collimation of the beam, use of lead clothing and dosimeter. The study suggests that the lack of regulation for the practice of veterinary radiology and lack of information may culminate to a compromise in radiological safety.